(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
This research examines the failure of the rise of the humane in Joumana Haddad’s play Kafas (Cages 2014) under patriarchy and second-wave feminism or what is known as radical feminism. The humane, Haddad’s project for a better world, requires humans to rise above their social and religious upbringing and to break free from conventional gender roles. In Kafas, both patriarchy and radical feminism fail to put the humane at the fore front of their creed and methods of operation. Instead, their very identity, agenda, and structure rely on the perpetuation of sexism, stigmatization, and victimization. Hence, the title of the play “Kafas” came to expose these practices and the indoctrination that women and men are subjugated to and suffer from.